Karakteristik Gelombang Laut di Perairan Pantai Samudera Indah Kabupaten Bengkayang Kalimantan Barat: Karakteristik Gelombang Laut di Perairan Pantai Samudera Indah Kabupaten Bengkayang Kalimantan Barat - Adriat, Riza; Muhardi, Muhardi; Risko, Risko; Ramat, Muhammad Farhan (Jurusan Ilmu Kelautan dan Perikanan Politeknik Negeri Pontianak, 2024)
Ocean coastal waters are coastal areas that have an important role economically and environmentally, with activities such as fisheries, tourism, and sea transportation. These waters often experience sea wave phenomena which have an impact on human activities, coastal infrastructure, and marine ecosystems. This research aims to determine the characteristics of sea waves in the coastal waters of Samudera Indah, Bengkayang Regency, West Kalimantan. The data used in this study on the characteristics of ocean waves are primary data and secondary data. The data is wind data for 10 years (2012 – 2022) which comes from data from the European Center for Medium-Range Weather Forecasts (ECMWF). Forecasting and determining the characteristics of sea waves is carried out using the Sverdrup Munk Bretschneider (SMB) method which is obtained from wind data. Based on analysis of wind data from 2012 to 2022, the height and period of significant sea waves in the west season are generally greater than in other seasons, namely 0.37 meters and 2.74 seconds. On the other hand, the average height and period of significant sea waves in transition season I are lower compared to the west season, east season and transition season II.